2020
DOI: 10.1080/00343404.2020.1813883
|View full text |Cite
|
Sign up to set email alerts
|

Analysing vote-choice in a multinational state: national identity and territorial differentiation in the 2016 Brexit vote

Abstract: Striking territorial variations in the 2016 Brexit referendum are neglected in the explanatory literature, a gap our analysis of British Election Study helps to fill. Rather than modelling Britain as one political system, we present parallel models for England, Scotland and Wales.Typical in other multi-national states, this approach is innovative for 'British politics'. To analyse complex multi-level national identities, we develop a Relative Territorial Identity (RTI) measure. Substantively, RTI predicts Brex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 62 publications
2
12
0
Order By: Relevance
“…The fact that sub‐state nationalist parties apparently address more than one issue almost inevitably implies that they cannot reach full congruence with public opinion on their single core issue of centre–periphery relations. With this conclusion, we are fully in line with earlier research results on Scotland (Henderson et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The fact that sub‐state nationalist parties apparently address more than one issue almost inevitably implies that they cannot reach full congruence with public opinion on their single core issue of centre–periphery relations. With this conclusion, we are fully in line with earlier research results on Scotland (Henderson et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…Recent research indeed suggests that there might not be a perfect correlation between the scores of sub‐state nationalist parties and public opinion with regard to their core issues. Studies show that the rise of nationalist parties does not automatically imply an increased support for secessionism (Henderson et al, 2021; Medeiros et al, 2022).…”
Section: The Multidimensional Appeal Of Sub‐state Nationalist Partiesmentioning
confidence: 99%
“…But the decision to leave the EU on 23 June 2016 would further shape Scottish politics in significant ways. Brexit exposed territorial differentiation in preferences on EU membershipwith 62% of Scottish citizens opting for Remain (McHarg and Mitchell 2017, 513) -which the referendum was not designed to take into account (Henderson et al 2021(Henderson et al , 1502, producing a mismatch between what Scottish citizens had voted for and what the UK government claimed it had a mandate to deliver (Curtice 2020, 225;McEwen 2018, 66). Scottish designs on Brexit, including continued membership of the Single Market and the Customs Union (Scottish Government 2016), were compatible with May's refusal to countenance territorial differentiation in the final agreement (McEwen 2021(McEwen , 1542(McEwen -1543Wincott et al 2021Wincott et al , 1533.…”
Section: Brexit and The Devolved Settlementmentioning
confidence: 99%
“…Most of the existing scholarship has focused on the detrimental effect Brexit has had on the devolved administrations (McEwen 2018, 66;McHarg and Mitchell 2017, 518;Salamone 2020, 17) or on the distinctions between Brexit and independence, with talk of 'irreconcilable sovereignties' (McEwen 2022), 'discordant goals' (Kenny and Sheldon 2021, 966), divergent territorial preferences (Daniels and Kuo 2021;Henderson et al 2021) and 'rival economic nationalisms' (Rioux 2020). The debate within the policy community has done little to rectify this gap, perhaps unsurprisingly, given the political difficulties of equating Brexit -a helpful recruiting tool for the independence cause -with Scottish nationalism.…”
Section: Independence As Brexit? the Politics Of Analogiesmentioning
confidence: 99%
“…In Scotland, by contrast, identity was related to Brexit preferences, but in a less divisive way. Henderson et al found strong Scottish identity, relative to British identity, to be a predictor of the Remain vote in Scotland, but with far less effect than the much stronger explanatory power of English identity among Leavers in England (Henderson et al, 2020). The prevalence of Scottish identity across the political spectrum has traditionally made it a relatively weak predictor of vote choice (McCrone, 2017).…”
Section: Exit From Brexit: Exit Strategies After the Eu Referendummentioning
confidence: 99%